Neuroprotective properties of Loranthus parasiticus aqueous fraction against oxidative stress-induced damage in NG108-15 cells - Wong, D.Z.; Kadir, H.A.; Lee, C.L.; Goh, B.H. (Springer Verlag (Germany), 2012)
Loranthus parasiticus, a Chinese folk medicine, has been widely used for the treatment of brain diseases, particularly in southwest China. Hence, the present neuroprotection model was designed to investigate its neuroprotective properties against H(2)O(2)-induced oxidative stress in NG108-15 cells. L. parasiticus aqueous fraction (LPAF), which was selected in the present study, had proved to be the most active fraction among the other tested extracts and fractions in our previous screening. The restoration of depleted intracellular glutathione (GSH), a major endogenous antioxidant, by LPAF was observed after H(2)O(2) insult. Pretreatment with LPAF substantially reduced the production of intracellular reactive oxygen species generated from H(2)O(2). Apoptotic features such as externalization of phosphatidylserine and disruption of mitochondrial membrane potential were significantly attenuated by LPAF. In addition, cell cycle analysis revealed a prominent decrease in the H(2)O(2)-induced sub-G(1) population by LPAF. Moreover, apoptotic morphological analysis by DAPI nuclear staining demonstrated that NG108-15 cells treated with H(2)O(2) exhibited apoptotic features, while such changes were greatly reduced in cells pretreated with LPAF. Taken together, these findings confirmed that LPAF exerts marked neuroprotective activity, which raises the possibility of potential therapeutic application of LPAF for managing oxidative stress-related neurological disorders and supports the traditional use of L. parasiticus in treating brain-related diseases.